تأثير دور الزوجين في عملية إتخاذ القرارات الشرائية للسلع المعمرة في الأسر الجزائرية - الزروق الزغيمي مريم (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2018)
مستخلص البحث يتناول هذا البحث أثر دور الزوجين داخل الأسر الجزائرية في عملية اتخاذ القرار الأسري المتعلق باقتناء الأجهزة الكبرى المعروضة في المتاجر، وتحديداً حالة الأجهزة الكهرومنزلية. تكتسي هذه الدراسة أهميتها من كونها توضح تأثير تفاعل الزوجين، وتوزيع أدوارهما وتأثير كل منهما على الآخر خلال المراحل المختلفة لعملية اتخاذ القرار، كما تسلط الضوء على العوامل المؤثرة في اتخاذ القرار الخاص باقتناء الأجهزة الكهرومنزلية. ولمعالجة إشكالية الدراسة، تم إجراء مسح ميداني عبر استمارة استبيان استهدفت عينة من المستهلكين في الأسر الجزائرية (أزواج وزوجات من نفس الأسر)، حيث عولج 250 استبياناً. وقد أُجري المسح بناءً على المراحل الثلاث لعملية اتخاذ القرار الأسري، بما في ذلك مدى تأثير مصادر المعلومات والمعايير المختلفة المتعلقة بالأجهزة الكهرومنزلية. ولاختبار فرضيات الدراسة، استخدمت المنهجية الوصفية التحليلية لقبول واختبار الفرضية الأولى للدراسة. وبناءً على تحليل العوامل باستخدام المكونات الأساسية، تم التوصل إلى مجموعة جديدة من العوامل المتعلقة بمصادر المعلومات، ومعايير اختيار الجهاز الأنسب، وقرار الشراء، والتي تتمثل في: الجماعات المرجعية، والعوامل المؤثرة في عملية التسويق، والعوامل المتعلقة بتأثير الشريك (الزوج أو الزوجة) في اتخاذ القرار، وعوامل تأثير أخرى (الخبرة والأطفال)، والمعايير المتعلقة بالتكلفة التقديرية، والمعايير المتعلقة بتصميم الجهاز وجودته، والمعايير المتعلقة بمنشأ العلامة التجارية وسمعتها، والمعايير المتعلقة بخدمة ما بعد البيع، فضلاً عن قرار الشراء الأحادي أو المشترك. وبناءً على هذه العوامل الجديدة، تم تصميم نموذج متكامل وتحليله بالاعتماد على منهج تحليل المسار (Path Analysis)، مما سمح بدوره بقبول الفرضية الثانية والثالثة للدراسة. الكلمات المفتاحية: الزوجان (الأسرة)، عملية اتخاذ القرار الأسري، السلع المعروضة، الأجهزة الكهرومنزلية.ABSTRACT This study deals with the influence of the role of the couple within the Algerian families in the household decision making process with respect to the acquisition of major households displays in shops , and in particular, the case of the electrical household appliances . This research is important because it shows the influence of spouses’ interactions, their role distributions and their influence on each other during the different steps involved in the decision-making process. It underlines the factors affecting the decision making regarding the acquisition of the electrical household appliances. Thus, to address the issue of the study, a survey was carried out via a questionnaire using a sample of consumers of Algerian households, both husbands and wives from the same families and 250 questionnaires were processed. The survey was conducted based on the three phases of the household decision making process, including the range of the influence of the sources of information and the various standards related to the household electrical appliances. To validate the hypotheses of the study, descriptive analytical methods were used to accept and test the first hypothesis of the study. According to the factor analysis using the key components, we have obtained a new set of factors regarding the sources of information, the standards related to choose the most appropriate device and the purchase decision which are represented in: the references groups, the factors affecting the marketing process, the factor related to the partner’s influence on the decision making (husband or wife), and other factors of impact (experience and the children), the norms relating to the estimated cost, standards relating to the design and the quality of the device, the standards related to the origin and the reputation of the registered trade-mark, the norms relating to the after sales service, a unilateral acquisition decision or a joint purchase decision. On the basis of these new factors we have designed a complete model and it was analyzed relying on the path analysis approach, which in return allows us to accept the second and the third hypothesis of the study. Key words: the spouses (the family), the household decision making process, the good displayed, the electrical household appliances.
Keywords: الزوجان (الأسرة); عملية اتخاذ القرار الأسري; السلع المعروضة; الأجهزة الكهرومنزلية; القرارات الشرائية; السلع المعمرة في الأسر الجزائرية